Analysis of dynamic response of offshore wind turbines subjected to ship impacts and the corresponding protection measures: a review - Ma, Lu; Ding, Jieyi; Zhang, Xianfeng; Wang, Wubin; Zhao, Xiong; Sun, Chongbo; Yang, Yang (Frontiers in Energy Research, 2024)
Offshore wind energy is characterized by its clean and renewable nature, leading to rapid growth in the industry. However, the incidence of ship collisions with offshore wind turbines has also risen with the increasing number of offshore wind farms, particularly in commercial shipping lanes. To gain a thorough understanding of dynamic response between wind turbines and vessels, this paper extensively reviews studies related to wind turbine-ship collisions over the past two decades to cover four key aspects: (i) the fundamental requirements and background of collision analysis study, (ii) the analysis of dynamic response and collision characteristics of the fixedbottom and floating offshore wind turbines (OWTs) subjected to ship collision forces, respectively, (iii) the influence of key collision factors that include impact positions, initial ship kinetic energy and soil-structure interaction on the structural response for the wind turbines, and (iv) the discussion of protection measures to mitigate the collision damage of the substructure. The limitations in the existing studies are discussed and future research directions are suggested.